Starting off on the right foot: strong right-footers respond faster with the right foot to positive words and with the left foot to negative words - de la Vega, Irmgard; Graebe, Julia; Härtner, Leonie; Dudschig, Carolin; Kaup, Barbara (Frontiers in Psychology, 2015)
Recent studies have provided evidence for an association between valence and left/right modulated by handedness, which is predicted by the body-specificity hypothesis (Casasanto, 2009) and also reflected in response times. We investigated whether such a response facilitation can also be observed with foot responses. Right-footed participants classified positive and negative words according to their valence by pressing a key with their left or right foot. A significant interaction between valence and foot only emerged in the by-items analysis. However, when dividing participants into two groups depending on the strength of their footedness, an interaction between valence and left/right was observed for strong right-footers, who responded faster with the right foot to positive words, and with the left foot to negative words. No interaction emerged for weak right-footers. The results strongly support the assumption that fluency lies at the core of the association between valence and left/right.